How and why business should embrace effective altruism - Singer, Peter (Henry Stewart Talks, 2023)
Effective altruism, Ethics, Professional donor, Political donation, Democracy, 2016 US elections, Taxation, Foreign aid, Vilification, Moral obligation, Climate change, Shareholder perspective